A compact electron beam evaporator for carbon doping in solid source molecular beam epitaxy - Reuter, Dirk; Wieck, A. D.; Fischer, A. (Review of Scientific Instruments)

Mechanical stress and magnetism of ferromagnetic monolayers - Sander, D; Enders, A; Schmidthals, C; Reuter, Dirk; Kirschner, J (Surface Science)

Stranski-Krastanov layers of Fe on W(1 1 0): A combined MOKE, LEED, SAM and stress measurement investigation - Sander, D.; Enders, A.; Schmidthals, C.; Reuter, Dirk; Kirschner, J. (Journal of Magnetism and Magnetic Materials)

The correlation between mechanical stress and magnetic properties of ultrathin films - Sander, D; Skomski, R; Enders, A; Schmidthals, C; Reuter, Dirk; Kirschner, J (Journal of Physics D: Applied Physics)

Anisotropic diffusion of3dmetals on W(110): Competition between crystalline structure and surface steps - Reuter, Dirk; Gerth, G.; Kirschner, J. (Physical Review B)

Formation of copper crystallites on a Cu/Fe/Cu(100) sandwich - Wiessner, A.; Agne, M.; Reuter, Dirk; Kirschner, J. (Surface Science)

Modifying diffusion anisotropies: Cap layer induced changes in spreading anisotropies - Reuter, Dirk; Gerth, G.; Kirschner, J. (Journal of Applied Physics)

Good/Bad Girls and their Fathers - Tönnies, Merle (Journal for the Study of British Cultures)

Laughter in Nineteenth-Century British Theatre: From Genial Blending to Harsh Distinctions - Tönnies, Merle (Internationale Forschungen zur Allgemeinen und Vergleichenden Literaturwissenschaft)

The 'Sensationalist Theatre of Cruelty' in 1990s Britain, its 1960s Forebears and the Beginning of the 21st Century - Tönnies, Merle (Contemporary Drama in English)

Betriebsprojekttage – Lernortkooperation im Gewerk Friseur/in: Projektaufgaben im Pflegebereich und Überlegungen zu deren Einsatzmöglichkeiten in Berufsbildenden Schulen - Beutner, Marc (Aktuelle arbeits-, berufs- und bildungsbezogene Herausforderungen an das Berufsfeld Körperpflege in der Dienstleistungs- und Wissenschaftsgesellschaft)

Ausbildungsbereitschaft in Klein- und Mittelunternehmen – Ausgewählte Ergebnisse einer Längsschnittuntersuchung 1999 und 2000 - Beutner, Marc (Berufsbildung im Handwerk: Kontinuität und Perspektiven)

Qualität der Ausbildung in der europäischen Union: Ergebnisse aus einer Vergleichsstudie - Beutner, Marc; Fischer, A (Berufsbildung im Handwerk: Kontinuität und Perspektiven)

Voigts-Virchow, E. (Hg.): Mediated Drama. Dramatized Media, 2000 - Tönnies, Merle (Forum Modernes Theater)

M-SCTP: Design and prototypical implementation of an end-to-end mobility concept - Xing, Wei; Karl, Holger; Wolisz, Adam; Müller, Harald (In Proc. 5th Intl. Workshop The Internet Challenge: Technology and Applications)

Sluggish Consumers: An Evolutionary Solution to the Bertrand Paradox - Hehenkamp, Burkhard (Games and Economic Behavior)

Light Propagation- and Many-particle-induced Non-Lorentzian Lineshapes in Semiconductor Nanooptics - Förstner, Jens; Ahn, K.J.; Danckwerts, J.; Schaarschmidt, M.; Waldmüller, I.; Weber, C.; Knorr, A. (physica status solidi (b))
The occurrence of non-Lorentzian lineshapes is analyzed for a variety of nanooptical semiconductor systems such as quantum wells and quantum dots. Their origin is traced back to light–matter interaction (light propagation) and many-particle correlations (electron–electron and electron– phonon interaction).
Keywords: tet_topic_polariton

Theory of ultrafast dynamics and lineshape of semiconductor quantum well intersubband emitters - Waldmüller, Ines; Förstner, Jens; Knorr, Andreas (Nonlinear Optics: Materials, Fundamentals and Applications)
On the basis of a density matrix approach including electron-electron scattering, a detailed analysis of the temporal dynamics and the dephasing process after optical excitation in intersubband emitters is presented for a wide range of parameters.
Keywords: tet_topic_qw

Coherent nonlinear pulse propagation on a free-exciton resonance in a semiconductor - Nielsen, N. C.; Linden, S.; Kuhl, J.; Förstner, Jens; Knorr, A.; Koch, S. W.; Giessen, H. (Physical Review B)
The coherent exciton-light coupling in pulse propagation experiments on the A-exciton resonance in bulk CdSe is investigated over a broad intensity range. At low light intensities, polariton propagation beats due to interference between excited states on both polariton branches are observed. In an intermediate intensity regime, the temporal polariton beating is suppressed in consequence of exciton-exciton interaction. At the highest light intensities, self-induced transmission and multiple pulse breakup are identified as a signature for carrier density Rabi flopping. Exciton-phonon scattering is shown to gradually eliminate coherent nonlinear propagation effects due to enhanced dephasing of the excitonic polarization. Calculations using the semiconductor Maxwell-Bloch equations are in qualitative agreement with the experimental data.
Keywords: tet_topic_polariton

Nonlinear Pulse Propagation in Semiconductors: Hole Burning within a Homogeneous Line - Förstner, Jens; Knorr, A.; Koch, S. W. (Physical Review Letters)
Features reminiscent of spectral hole burning in a homogeneous line are predicted to result from the interaction of small area pulses with the semiconductor exciton resonance. The small area pulses may be designed through pulse shaping or evolve naturally in bulk semiconductors via polaritonic effects. The spectral features exhibit signatures that are characteristic for the underlying material nonlinearity and should occur in any system with isolated spectral resonances and coherent nonlinearities.
Keywords: tet_topic_polariton